Association of VDR gene polymorphisms and 22 bp deletions in the promoter region of TLR2Δ22 (‐196‐174) with increased risk of pulmonary tuberculosis: A case‐control study in tea garden communities of Assam. Issue 7 (4th May 2018) - Devi, Kangjam Rekha; Mukherjee, Kaustab; Chelleng, Pradipta Kumar; Kalita, Simanta; Das, Upasana; Narain, Kanwar
Abstract : Background: A high number of pulmonary tuberculosis (PTB) cases have been reported from tea garden communities of Assam. Till date, no molecular epidemiological study was performed to investigate the association of candidate gene(s) with the risk PTB in this region. The present case‐control study was aimed to investigate the association of vitamin D receptor ( VDR) gene polymorphisms and 22 bp deletion in the promoter region of toll‐like receptor 2 ( TLR2) gene with the risk of PTB in tea garden communities of Assam. Methods: Genotyping of VDR polymorphisms and TLR2Δ22 (‐196‐174) gene was carried out for 169 PTB cases and 227 apparently healthy community controls using blood samples by PCR‐RFLP followed by DNA sequencing. For association study, both univariate and multivariate logistic regression analyses were performed. Results: This study has shown that BsmI and FokI polymorphisms of VDR gene significantly associated with an increased risk of PTB (AOR = 3.58, 95% CI = 1.64‐7.80, P  < .01 for B/b genotype of BsmI and AOR = 2.44, 95% CI = 1.40‐4.24, P  < .01 for F/f genotype of FokI polymorphism). No significant association of TaqI and ApaI polymorphism of VDR gene was found with the risk of PTB. Moreover, this study has revealed that person carrying deletion allele in their TLR2Δ22 (‐196‐174) gene is significantly associated with an increased risk of PTB having b/b or F/f genotypes in BsmI or FokI polymorphisms of VDR gene. Conclusion: This study has revealed that BsmI and FokI polymorphisms of VDR gene significantly associated with an increased risk of PTB.